Methods of testing plastics. Thermoplastics pipes, fittings and valves. Method of test for the change in mass of unplasticized polyvinyl chloride pipes and fittings on immersion in sulphuric acid Part 11 Method 1105A, (28th February 1983) - British Standards Institution,
No abstract available